How perceived eWOM in visual form influences online purchase intention on social media: A research based on the SOR theory - Chi Thanh Bui; Thi Thuy An Ngo; Huynh Khanh Long Chau; Nguyen Phuc Nguyen Tran (PLoS ONE, 2025)
In today’s digital landscape, visual content plays a crucial role in shaping consumer behavior. This study explores how visual electronic word-of-mouth (eWOM) on social media influences online purchase intention, applying the Stimulus-Organism-Response (SOR) framework. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data from 335 social media users, this study examines the effects of visual eWOM’s quality, quantity, and credibility on consumer perceptions, attitudes, and ultimately their purchase intentions. Our findings reveal that the quality and credibility of visual eWOM significantly enhance perceived information usefulness and its adoption by consumers. Information quantity, however, primarily influences attitudes towards the information, but does not directly drive its adoption. Contrary to expectations, information usefulness alone cannot predict purchase intention. Instead, information adoption emerges as a key mediator, indicating that consumers must actively engage with and internalize visual content for it to impact their buying behavior. This underscores that the effectiveness of visual eWOM is not solely based on its characteristics but depends on consumers’ active engagement and processing. These insights highlight the need for content that is not only visually appealing but also credible and engaging to facilitate information adoption and drive purchase intentions. This study enhances the understanding of visual eWOM’s impact on online purchasing and provides valuable insights for marketers aiming to optimize digital engagement strategies.